(untitled) (World Bulletin of Public Health, 2023)
Understanding the nature and structure of communicative skills allows to understand what conditions are necessary for its effective development among future primary school teachers. Within this study, the process of developing communicative skills of future teachers is considered as a targeted influence on the student’s personality. In addition, it is understood that during the learning process, students go through and further process the received information. At this stage, the processes of personal activity are activated, which means constant work on oneself and self-development. According to this position, the student is considered not only as a subject of educational and professional activity, but also as a subject of continuous active self-development. The teaching profession is distinguished by a constantly evolving component that is not present in all professions. Students of the psychological and pedagogical direction of education should know the need for continuous self-improvement and self-development in the future profession, without which it is impossible to achieve the desired results of professional activity